Movie Review Harmony (2010), Director: Kang Dae Kyu, Script Writers: Lee Seung Yeon, Yoon Je Kyun, Kim Whee, and Kang Dae Kyu, Production: CJ Entertainment Korea - Ramadhani, Defarah Kamila; Ifandi, Muhammad Fajar; Az Shaidah, Zahra (Faculty of Law Universitas Negeri Semarang, 2021)
This film tells the story of life in a women's prison. It shows how much trauma and remorse are in the prisoners. The main character is Jeong Hye, she is imprisoned for killing her violent husband. Jeong Hye also lives with several other inmates in one cell.